Tinjauan Potensi Pajak Penghasilan Orang Pribadi Pengguna Aplikasi Snack Video - Nanda Efri Liani; Johannes Aritonang (JURNAL PAJAK INDONESIA, 2022)
This study aims to determine the business process of earning income from the Snack Video application, the potential income tax (PPh) that can be extracted from the Snack Video application, and the mechanism for calculating income tax from the Snack Video application. Data obtained from the results of interviews, application usage, and user reviews of the Snack Video application, and some literature. The potential imposition of income tax depends on how much income the application user receives. Until this paper was compiled, there were no more specific regulations regarding the imposition of income tax for private people who use the Snack Video application. However, based on existing regulations, the potential income tax of individuals from the Snack Video application can be classified as a tax object of article 4 paragraph (1) and article 4 paragraph (2) of the Income Tax Law. The provisions that can be used are in accordance with the Income Tax Law Article 4 paragraph (2), Article 14, Article 16, Article 17 paragraph (1), Government Regulation (PP) Number 23 of 2018, and further regulations from the article which are set more specifically in the regulations of the Directorate General of Taxes (DGT).